Audit and Certification of Geographically Indicated Agricultural Products: The Case of Malatya Apricot (Third Sector Social Economic Review, 2025)
Geographical indication registration ensures the market recognition of a product based on its quality, traditional characteristics, and regional attributes. In recent years, the number of geographical indication–registered products has been increasing rapidly. However, in the absence of an effective control mechanism for the use of geographical indications, consumer trust is undermined, unfair competition intensifies, and genuine producers are adversely affected. Therefore, achieving the expected benefits of geographical indications depends on the existence of an efficient inspection system. This study designs the core components of a certification program that would enable the audit and certification of geographical indication products by an accredited body in accordance with the TS EN ISO/IEC 17065 standard. The main purpose of this study is to design a sample certification program to strengthen the inspection mechanism within the framework of the special characteristics determined by geographical indication registration conditions and to ensure that products offered to the market are subjected to a certification cycle that establishes consumer confidence. The “Malatya Apricot,” registered as a geographical indication both in Türkiye and the European Union, was selected as a case study in determining the main principles of the program. A survey was conducted with 80 apricot enterprises in Malatya, which ranks first in the world in apricot production and exports, using a sampling method. According to the survey results, 47.50% of enterprises use the geographical indication, while 52.50% do not. Among those not using it, 35.71% stated that their marketing channels did not require it, 33.33% felt no need for it, and 30.95% lacked sufficient knowledge on the subject. In contrast, 85.00% of enterprises indicated that they would request certification of the “Malatya Apricot” geographical indication if a certification program were established. These findings reveal that the development of an accredited certification program for geographical indication products is a significant necessity for both producers and consumers.
Keywords: Geographical Indication; Accreditation; Audit; Certification; Malatya Apricot